Historical Overview of Nursing Education in Nepal - Shrestha, Sarala (Journal of Nursing Education of Nepal, 2022)
In the changing world, history is the key to understand the trend in any society. History of nursing education helps to understand how nursing education has progressed from past to present. The objective of this reviewarticle is to briefly describe the initiation and progression of nursing education in Nepal with special focus on trends in nursing education in Maharajgunj Nursing Campus, the first institution for nursing education in Nepal.